2016
DOI: 10.5194/nhess-2015-320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rainfall feature extraction using cluster analysis and its application on displacement prediction for a cleavage-parallel landslide in the Three-Gorges Reservoir area

Abstract: Abstract. Rainfall is one of the most important factors controlling landslide deformation and failure. State-of-art rainfall data collection is a common practice in modern landslide research world-wide. Nevertheless, in spite of the availability of high-accuracy rainfall data, it is not a trivial process to diligently incorporate rainfall data in predicting landslide stability due to large quantity, tremendous variety, and wealth multiplicity of rainfall data. Up to date, most of the pre-process procedure of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…within each group in a data set [59]. The main idea behind the k-means algorithm is grouping n points of m dimensions into k clusters, so that for each cluster, the square of the Euclidean distance between the x points that belongs to n and the centroid of the cluster is minimal (Equation (1)) [58,60,61].…”
Section: Clustering Approach: K-means Algorithmmentioning
confidence: 99%
“…within each group in a data set [59]. The main idea behind the k-means algorithm is grouping n points of m dimensions into k clusters, so that for each cluster, the square of the Euclidean distance between the x points that belongs to n and the centroid of the cluster is minimal (Equation (1)) [58,60,61].…”
Section: Clustering Approach: K-means Algorithmmentioning
confidence: 99%
“…To address such challenges in these areas, the literature accentuates the importance of adopting more water-saving technologies through the efficient storage and use of water [11]. Several studies described STRV on different scales [12][13][14][15][16]; however, these studies rarely demonstrated the potential relationship between STRV and yield variability among farmer fields located within the same agricultural watershed. Rainfall studies in the forms of trend analyses and spatial variability over large areas are numerous, but these studies have limited connections to local agricultural challenges.…”
Section: Introductionmentioning
confidence: 99%